THE ROLE OF WOMEN'S COFFEE COOPERATIVES (KOKOWA) TOWARD THE WELFARE OF COFFEE FARMERS IN BUKIT DISTRICT, BENER MERIAH REGENCY - Tambarta, Emmia; Hafni Zahara; Ade Firmansyah Tanjung; Erika Safira; Tri Arini Utami (RADJA PUBLIKA, 2022)
The existence of cooperatives in coffee production, centers is expected to support and help the economy of coffee farmers. One of the best coffee producing areas in Indonesia is Aceh Province, this is proven because coffee produced in Aceh has been exported to various countries such as Europe. America and countries in Asia. Aceh coffee which is better known internationally is the type of Gayo Arabica coffee because it has a distinctive aroma and taste. (Tambarta, 2016) The name Gayo Arabica coffee arises because the best-tasting Arabica coffee comes from the Gayo highlands, namely Central Aceh and Bener Meriah districts. This research uses descriptive quantitative research methods. Quantitative descriptive is a method that describes the research topic with variables that can be measured quantitatively (Sugiyono, 2011). The research was conducted at the Women's Coffee Cooperative (KOKOWA) Bener Meriah Regency. This location was determined intentionally or purposively because the KOKOWA Cooperative is the only cooperative whose members are all housewives and coffee farmers (having dual roles). The method used in analyzing the data is descriptive qualitative analysis using a Likert scale instrument, which describes several question items arranged in a questionnaire and each question is given a score equal to the respondent's choice. Likert scale is a scale used to measure attitudes, opinions and perceptions of a group of people about social events or phenomena. This research produces TKT 1 with output targets in the form of (1) scientific publications in international research journals with accepted status, (2) HKI research reports with granted status, (3) publication of activities in print or online media.